Updated distribution of the Texas kangaroo rat (Dipodomys elator) and patterns of rodent species associations from county road surveys in Texas - Stuhler, John D.; Halsey, Michaela K.; Goetze, Jim R.; Bradley, Robert D.; Ray, David A.; Stevens, Richard D. (THERYA, 2023)
The Texas kangaroo rat (Dipodomys elator) is a rare species of conservation interest at both the state and federal level. Therefore, an updated understanding of distribution and abundance of D. elator is critical for initiating informed decisions about its conservation status and subsequent management strategies. We surveyed more than 850 locations along unpaved county roads across the historical range of this species in north-central Texas to identify sites of D. elator presence and examine patterns of rodent species associations. We determined that D. elator presently occurs in five counties in Texas within its historical range and was the eighth most abundant species of the 14 species that we captured. Moreover, we found that the majority of pairwise species associations, including those involving D. elator, were random and there was no strong evidence that pairs of rodents were aggregating or segregating with respect to each other. We did observe negative associations between D. elator and both Dipodomys ordii (Ord’s kangaroo rat) and Sigmodon hispidus (hispid cotton rat). Nonetheless, these patterns indicate that interspecific interactions do not play a strong role in influencing the distribution of D. elator. However, the restricted and temporally dynamic distribution of this species suggests that a metapopulation perspective should be considered when making future conservation considerations.